Can green technologies serve as a pathway for women’s socioeconomic inclusion in Africa? - Donald, Djatcho Siefu; Orfe, Chouafi Nguekam; Merime, Aguekam Ngako; Chretien, Nzomo Tchuenta Joseph (Asian Journal of Economics and Empirical Research, 2024)
This study aims to evaluate the effects of green technology innovations on the socio-economic integration of women in Africa from 2014 to 2023. To achieve this goal, a quantitative analysis of longitudinal data has been utilized through econometric techniques such as fixed effects models, Lewbel 2SLS (Two Stage Least Square) 2SLS estimates, and panel quantile models to address and mitigate potential endogeneity bias. The findings show a direct impact on women’s employment in high- and middle-income countries, particularly in renewable energy generation and sustainable agriculture, as a result of increased use of green technologies. Additionally, in these countries, better availability of renewable energy is related to the advancements made by women’s education and household health. Yet, access to the economic opportunities that this technology enables for many women in lower-income parts of the world remains scarce. Hence, it is necessary to mainstream gender and institutional issues more into the green technology policies in Africa. It would lead to a fairer sharing of the socio-economic gains arising out of green technology adoption and help in promoting sustainable development.